Pengaruh Media Sosial Tiktok Terhadap Hasil Belajar PAI Siswa UPT SDN 12 Arungkeke Kabupaten Jeneponto - Ashar Ashar; Roslyn Roslyn; Ayma Ayma (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this research is to determine the influence of TikTok social media on student learning outcomes in Islamic religious education subjects at UPT SDN 12 Arungkeke, Jeneponto Regency. This type of research is quantitative survey/expost facto research. Research procedures include the conceptual phase, design and planning phase, creating instruments and collecting research data, empirical phase, analytical phase (analyzing data and calculating research data results), and dissemination phase (designing research results). The research results show that the T test Judging from the value of Tcount (89.584) > Ttable (1.713) or the significant probability value of 0.000 < 0.05, then Ho is rejected and Ha is accepted, meaning that social media Tik Tok (X) has a positive and significant effect on student learning outcomes (Y). Based on student learning results and tests carried out by researchers, it can be seen that social media Tik Tok has an influence on student learning outcomes in Islamic religious education subjects at UPT SDN 12 Arungkeke, Jeneponto Regency.